Roles Conflict Among a Sample Of Women Working in Humanitarian work "A Field Study In The City Of Latakia" - فندي, إسراء; صفاء صبح ,; فاتن مشاعل , (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The primary purpose of this research is to identify the level of role conflict among a sample of women workers in the humanitarian field in the city of Latakia. Additionally, the study aims at identifying differences in the responses of the research sample according to several variables (socioeconomic status, nature of job function, years of experience). Thus, in order to achieve the research objectives, the researcher follows a descriptive methodology and designs a role conflict questionnaire based on previous studies, comprised of 40 items distributed across four dimensions. The research sample also consists of 100 female workers from the humanitarian organization, Mosaic Association for Relief and Humanitarian Services, in Latakia. The research concludes the following results: The level of role conflict among the sample members is average. There are differences in the level of role conflict among sample members depending on the variable of social status, in favor of widowed women. There are no differences between the average scores of female humanitarian workers on the Role Conflict Questionnaire depending on the variables of the nature of job work and the number of years of experience..